Nonprescription Stimulant Use at a Public University: Students’ Motives, Experiences, and Guilt - Cook, Carley (Journal of drug issues, 2021)
We examined the use of nonmedical prescription stimulants (NPSs) among students (N = 1,208) at a large public university in southeastern United States. After students who had been prescribed stimulants had been removed from the sample, 202 of the remaining 1,067 students (i.e., 18.9%) reported having engaged in NPS use in their lifetime. NPS use was strongly associated with membership in Greek societies and with binge drinking behavior. NPS users overwhelmingly reported engagement in NPS use for academic rather than for recreational purposes, and as anticipated, NPS users with academic motives reported stronger academic benefits than NPS users with social/recreational motives. Reports of guilt were low, and frequent users reported less guilt than infrequent users. Implications for interventions are discussed.